Chapter Migrazioni e politiche migratorie: uno sguardo europeo - Ambrosini, Maurizio (Studi e saggi, 2021)
In the coming years the European Union will be called to make challenging choices on three aspects of migration policies. The first is that of entry conditions, with particular reference to labour immigration.The second theme concerns the integration of immigrants already present on EU territory. The European Union will have to resolve issues such as greater harmonisation of criteria for naturalisation and access to local voting, especially with regard to second generations of immigrant origin.The third major arena for discussion concerns the issue of asylum and involves internal EU solidarity.